PARP inhibitors as radiosensitizers: a comprehensive review of preclinical evidence and clinical applications - Luo, Xiaodong; Gao, Shuo; Sun, Kaiyang; Dong, Zhiqiang; Yang, Shude (Frontiers in Oncology, 2025)
Poly (ADP ribose) polymerase 1 (PARP1) plays a central role in the response of DNA damage induced by tumor radiotherapy. This paper systematically reviewed the structural and functional characteristics of PARP1 and its molecular mechanism in DNA damage repair, and focused on the preclinical evidence and clinical transformation research progress of PARP inhibitor (parpi) as a radiosensitizer. PARP1 affects the effect of radiotherapy by recognizing DNA breakage, catalyzing par modification and regulating repair pathway, while parpi significantly enhances radiosensitivity by inhibiting DNA repair, inducing synthetic lethal effect and regulating immune microenvironment. Although preclinical studies have shown good prospects in a variety of solid tumors, clinical transformation still faces challenges such as heterogeneity of efficacy and drug resistance mechanism. Future research should focus on precise treatment strategies, joint scheme optimization and drug resistance mechanism exploration, so as to promote the wide application of parpi in radiotherapy. This article presents a narrative review of the preclinical and clinical evidence supporting the use of PARP inhibitors as radiosensitizers.